Systematic literature review and meta-analysis of dual therapy with fenofibrate or fenofibric acid and a statin versus a double or equivalent dose of statin monotherapy. (2nd December 2015) - Ouwens, Mario J.N.M.; Nauta, Jos; Ansquer, Jean-Claude; Driessen, Stefan
Abstract: Objective: To assess the efficacy of fenofibrate and statin dual therapy versus a double or equivalent dose of statin monotherapy. Methods: A systematic literature search and meta-analysis was performed for publications before 1 January 2014 in MEDLINE, Embase, and BIOSIS Previews, among others. Results: The difference in percentage change from baseline was in favor of dual therapy versus a double dose of statin monotherapy for triglycerides (difference −20%; standard error [SE] 2.6%) and HDL-C (8.7%; SE 1.2%), but not for LDL-C (8.4%; SE 1.5%), non-HDL-C (2.8%; SE 1.1%), total cholesterol (4.5%; SE 1.0%) and apolipoprotein B (2.6%; SE 1.1%). For high intensity statins, the difference in percentage change from baseline was in favor of dual therapy versus equivalent statin monotherapy for triglycerides (−17%; SE 2.6%) and for HDL-C (8.7%; SE 1.9%). The difference in percentage change from baseline for LDL-C was 6% (SE 1.7%), implying a greater reduction in LDL-C with statin monotherapy. For moderate intensity statins, the difference in percentage change from baseline was in favor of dual therapy versus equivalent statin monotherapy for triglycerides (−24.2%; SE 1.2%) and HDL-C (8.2%; SE 0.9%). LDL-C decreased 2.2% (SE 1.4%) more with dual therapy. Conclusions and implications of key findings: When aiming to change HDL-C or triglycerides, dual therapy is to be preferred to doubling the statin dose; conversely, doubling the statin dose is to be preferred when aiming to reduce LDL-C. If the aim is both to change HDL-C or triglycerides and to reduce LDL-C, the importance of the three outcomes may need to be weighed depending on the intensity of the statin. Combining high intensity statin therapy with fenofibrate improves the effect on HDL-C and triglycerides, but lowers the effect on LDL-C. Combining a moderate intensity statin with fenofibrate improves the effect on HDL-C and triglycerides without reducing the effect on LDL-C. There is a need for long-term randomized clinical trials to compare dual therapy versus doubling the statin dose to assess the importance of improvement in HDL-C and triglycerides versus improvement in LDL-C in terms of cardiovascular outcomes. Further, the addition of ezetimibe to statin/fenofibrate therapy may be of interest.